POTENSI PUPUK KOTORAN KELINCI DAN PUPUK ANORGANIK PADA TANAMAN TOMAT (Lycopersicum esculentum Mill.) : Pupuk kotoran kelinci, Pupuk anorganik,Tomat varietas Servo - Rahmatika, Widyana; Wasito, Wasito; Satriya Wibawa, Satriya Wibawa; Handayani, Tri; Fitriyah, Nur (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
The research was conducted from May to December 2023 at the UNISKA Kediri Field Laboratory. The aim of the research was to determine the interaction of giving organic fertilizer from rabbit droppings and inorganic fertilizer on tomato growth and production. The materials used are two types of rabbit manure, namely solid and liquid, inorganic fertilizer NPK 16:16:16 and tomato plant seeds. RAKF research method (Randomized Group Factorial Design). The first factor is rabbit manure fertilizer, consisting of two levels, the second factor is inorganic fertilizer consisting of 4 levels, so that 8 treatment combinations are obtained. After the data is obtained, an analysis of variance is carried out and continued with BNT 5% if there is a real influence on a single factor and a DMRT test is carried out if an interaction occurs. It was found that solid rabbit manure had a very significant effect on the number of leaves, plant height, stem diameter, number of fruit and fruit weight. Inorganic fertilizers have a significant effect on the number of leaves, plant height, stem diameter, number of fruit and fruit weight. The best rabbit manure treatment is solid rabbit manure (K1) and the best inorganic fertilizer treatment is NPK 16:16:16 fertilizer treatment with doses of 5 grams and 7.5 grams.